An automotive interior lighting application using white light-emitting diodes - Solomon, Ramzi; Pillay, P.; Sebitosi, A. B. (Cape Town : Cape Town University, 2010)
Thesis (MScEng (Department of Electrical Engineering))--University of Cape Town, 2008.